Presentations and management of hospitalized patients with upper extremity fractures at a level 1 trauma center: a 5-year observational study - Syed Imran Ghouri (22045343) (2024)
Background Upper extremity injuries (UEIs) are common in the emergency departments, yet they are under-reported in developing countries. This study examined the frequency, injury characteristics, and treatment approaches of upper extremity fractures (UEFs) among hospitalized trauma patients in a nationally representative population. Methods We conducted a retrospective, observational study including all the hospitalized patients with UEFs in the only level 1 trauma center in Qatar between July 2015 and August 2020. Comparative analyses were performed according to injury mechanisms, severity, and management approach. Results A total of 2,023 patients sustained UEIs with an average age of 34.4 ± 12.9 years, and 92% were males. Motor vehicle crashes (MVCs; 42.3%) were the primary cause of shoulder girdle injuries in 48.3% of cases. Fractures of the radius, ulna, and hands occurred in 30.8, 16.5 and 14.5%, respectively. Young adults were more involved in MVCs and motorcycle crashes (MCCs), while pedestrians who were typically older had a higher rate of humerus fractures. Patients with MCCs had a higher rate of clavicle and ulna fractures. Pedestrians were at risk of serious injuries, with a higher mean injury severity score and lower Glasgow Coma Scale. Conclusion Most UEFs patients were young males and mainly affected by MVCs. Shoulder girdle, particularly clavicle and scapula/glenoid fractures, emerged as common injury sites. The study highlighted the potential risk of pedestrian injuries, as reflected in higher injury severity, concomitant injuries, and higher mortality. Future studies are needed to optimize preventive measures by incorporating insights into specific injury mechanisms and patterns of UEIs. Other Information Published in: European Journal of Orthopaedic Surgery & Traumatology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00590-024-04017-2